Insights into salt perception and cognitive impairment among middle-aged and older adults: a scoping review - Azira Sazali; Suzana Shahar; Hasnah Haron; Nor Fadilah Rajab; Fatin Hanani Mazri; Theng Choon Ooi; Nurul Fatin Malek Rivan (BMC Public Health)
Abstract Background A decline in taste sensitivity from aging leads people with a higher salt threshold to frequently add more salt to their food, which attributed to decreased cognitive efficiency. This scoping review aimed to gather the latest evidence on the relationship between salt perception and cognitive impairment which is essential in the development of new intervention and prevention strategies. Methods Studies published between January 2014 and March 2024 were searched across four databases: PubMed, the Cochrane Library, Scopus, and EBSCO. Data extraction involved gathering details on the study design, participant demographics, methods for assessing cognitive function and salt perception, considering confounding factors, and synthesizing the primary outcomes. Results Six studies were included in the analysis, five cross-sectional studies and a longitudinal study. These studies revealed various associations between salt perception and cognitive impairment. Specifically, findings from a three-year longitudinal study suggested that lower salt sensitivity was associated with poorer cognitive scores, which is consistent with the results of two other studies. However, the remaining three studies did not find significant differences (p > 0.05) in salt taste perception related to cognitive status. Furthermore, a study identified executive function as another significant factor influencing salt taste perception. Conclusion These findings highlight the link between cognitive decline in salt perception, which provide an indication of salt intake and related health risks. There is a need to explore the mechanisms of salt taste sensitivity and its impact on cognitive health should be encouraged. Graphical Abstract